Three-dimensional kinematics of the knee and ankle joints for three consecutive push-offs during ice hockey skating starts - Lafontaine, D. (Sports Biomechanics, 2007)
Little biomechanical research has been conducted recently on hockey skating despite the sport's worldwide appeal. One reason for this lack of biomechanical knowledge stems from the difficulty of collecting data. The lack of accuracy, the disputable realism of treadmills, and the large field of view required are some of the technical challenges that have to be overcome. The main objective of the current study was to improve our knowledge of the joint kinematics during the skating stroke. A second objective was to improve the data collection system we developed and the third was to establish if a kinematic progression exists in the hockey skating stroke similar to that in speed skating. Relative motions at the knee and ankle joints were computed using a joint coordinate system approach. The differences at the knee joints in push-offs indicated that the skating skill was progressively changing with each push-off. The relative stability of the ankle angles can be attributed to the design of the skate boots, which have recently become very rigid. Further research on ice hockey skating is warranted and should include more skaters and investigate the effect various starting strategies and variations in equipment have on skaters' performance.